2022
DOI: 10.1080/17461391.2022.2081093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of external load on muscle activation during the barbell back squat

Abstract: The aim of this study was to compare gluteus maximus-to-hamstring (GM:H) co-activation, hamstrings-to-quadriceps (H:Q) co-activation, and mean muscle activity in the vastus lateralis (VL), vastus medialis (VM), rectus femoris (RM), gluteus maximus (GM), semitendinosus (ST), and bicep femoris (BF) muscles across a range of training loads (40%, 50%, 50%, 70%, 80% 90% 1RM) of the barbell back squat in resistance trained females. Surface electromyography (EMG) was observed in 18 healthy resistance trained females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
0
0
Order By: Relevance
“…In addition, even in exercises with large movements or those performed in a prone position, such as kick-backs, mountain climbs, and split jacks, there was a tendency for abdominal and lower-extremity muscle activity to be higher with the Bot Fit. This con rms previous ndings that resistance training increases trunk-and leg-muscle activation through increased external loading and higher training intensity 37 . These results emphasize the effectiveness of the Bot Fit in developing and strengthening target muscles and suggest its potential as a tool to enhance tness exercises.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, even in exercises with large movements or those performed in a prone position, such as kick-backs, mountain climbs, and split jacks, there was a tendency for abdominal and lower-extremity muscle activity to be higher with the Bot Fit. This con rms previous ndings that resistance training increases trunk-and leg-muscle activation through increased external loading and higher training intensity 37 . These results emphasize the effectiveness of the Bot Fit in developing and strengthening target muscles and suggest its potential as a tool to enhance tness exercises.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is unclear if technique remains consistent across the entire spectrum of these loads when training to, or near voluntary failure. Earlier research supports the assumption that technical variations depend on load, as evidenced by the influence of load on EMG signals ( Mehls et al, 2021 ; Martinez, Coons & Mehls, 2023 ). Repetition range might influence joint and barbell kinematics and EMG amplitude during different phases of the lift due to compensatory strategies, which are indirect measures ( Morton et al, 2019 ; Larsen, Haugen & van den Tillaar, 2022 ) of understanding differences between a given repetition range and 1RM squat strength.…”
Section: Introductionsupporting
confidence: 54%
“…A final potential reason the current study did not see a significant difference in muscle activity is low absolute loading. It has been well established that as external load on the body or a muscle increase, muscle activity also increases (19). The functional movements tested in this study did not apply any external loading above the participants bodyweight.…”
Section: Discussionmentioning
confidence: 81%
“…To the author's knowledge, only one study has observed the effects of restricted hip extension on muscle activity during functional movement patterns (a bilateral air squat) (17). Additionally, it has been noted that males and females adopt different strategies to complete movements for a variety of reasons and that females have higher rates of lower extremity injury than males (18,19). To better understand the effects of restricted hip extension on muscle activity in healthy females during functional movements, further investigation is required.…”
Section: Objectivesmentioning
confidence: 99%